A Warm and A Cold Spot in Cape Cod Waters Amid the Recent New England Shelf Warming - Yu, Lisan; Yang, Kristine T. (Frontiers in Marine Science, 2022)
Despite the widely recognized warming of the New England Continental Shelf (NES), climate patterns of the shelf’s economically and ecologically important coastal environments remain less examined. Here we use a satellite sea-surface temperature (SST) analysis gridded on 0.05-degree spatial resolution to show, for the first time, the existence of a warm and a cold blob in the environs of Cape Cod, Massachusetts amid the NES warming of the past 15 years. The warm blob refers to an increasing warming trend in shallow waters of Nantucket Sound sheltered by the islands of Martha’s Vineyard and Nantucket. The summer SST maxima have increased by 3.1 ± 1.1C (p<0.1), about three times faster than the warming elsewhere on the NES, and the summer season has lengthened by 20 ± 7 days (p<0.1). The cold blob refers to an increasing cooling trend over Nantucket Shoals, an area of shallow sandy shelf that extends south and southeast from Nantucket Island and also known for strong tidal mixing. The strong cooling trend during June–August reduced the SST maxima by -2.5 ± 1.2C (p<0.1) and shortened the warm season by -32 ± 11 days (p<0.1). Away from the Cape Cod waters, the broad warming on the shelf is attributable to a forward shifted annual cycle. The shift is most significant in August–November, during which the summer temperatures lingered longer into the fall, producing a pronounced warming and delaying the onset of the fall season by 13 ± 6 days (p<0.1). The three different patterns of SST phenology trends displayed by the respective warm blob, the cold blob, and the broad shelf highlight the highly dynamically diverse responses of coastal waters under climate warming. Finally, the study showed that spatial resolution of SST datasets affects the characterization of the spatial heterogeneity in the nearshore SSTs. The widely used Optimum Interpolation SST (OISST) on 0.25-degree resolution was examined. Although the two SST datasets agree well with the measurements from the moored buoys at four locations, OISST does not have the cold blob and shows a higher rate of warming on the shelf.